The factors effecting the discovery of insurance fraud from the perspective of the National Insurance Company's employees (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to identify the factors effecting the investigation of insurance fraud from the perspective of the National Insurance Company employees, by analyzing the study variables and make recommendations on how to enhance the company and employees performance, and to achieve the objectives of the study and test hypotheses a questionnaire was designed after referring to the international standards  and the 1969 Iraqi punishment law, and it was answered by 20 employees that were approved for the purposes of  this research and analysis.      The study found that lack of employee training was a strong factor, while the supervisory staff and operational procedures was a weak one.Given the scarcity of available data on the reality of fraud in the local insurance companies a personal interviews used to obtain information relevant to the research, the study found that during the period 2000 - 2010 several fraud cases was discovered in the National Insurance Company using variety of methods depending on circumstances and insurance type.     The study concluded with some recommendations to the insurance company and employees to enhance performance.